Análise proteômica do plasma seminal e secreções do epidídimo em ruminantes: potenciais associações com o desenvolvimento sexual, parâmetros seminais e função espermatica - Souza, Carlos Eduardo Azevedo (2007)
This research includes three different studies, evaluating distinct aspects about the composition of proteins expressed in the ruminant reproductive tract fluids. The first study describes variations in the seminal plasma protein profile of Santa Inês rams. The second identifies proteins present in the cauda epididymal fluid of Holstein bulls, and the third study details the binding pattern of BSPs and osteopontin to bovine sperm membrane. In Study 1, semen samples of sixteen rams were collected and centrifuged to obtain seminal plasma. A volume containing 150 μg of proteins was used to prepare the 2D gels, which were scanned and electronically analyzed. The quantification of the protein spots was given as PPM of the total integrated optical density. We detected 186 ± 10 spots in the gels prepared with the 48 weeks samples, similar to the amount found in the gels obtained from samples of 34 (183) and 30 (179) weeks of age. Maps representing 34 and 48 weeks showed a train of spots with 63 kDa (pI 4.2 to 5.0) that was not present in early ages. New proteins were detected in the gels as the rams matured. In the maps of 20 weeks, high molecular weight trains (158 to 160 kDa) were detected compared to other gels obtained before that age. Quantitative changes in the spots with age were more evident before puberty. We also described a relationship between the intensity of some spots in the 48-week maps and semen scores. We conclude that protein secretion in the seminal plasma of hairy rams is synchronized with a series of complex changes during the sexual development of the males. The objective of Study 2 was to describe the binding pattern of OPN and BSP proteins to the membrane of ejaculated bovine sperm and after in vitro exposure of these cells to bovine oviductal fluid. Semen samples of five Holstein bulls were obtained and subjected to the following treatments: 1. Ejaculated sperm; 2. Ejaculated sperm incubated with isthmus oviductal fluid; 3. Ejaculated sperm incubated sequentially with isthmus and ampullary oviductal fluid. From each of these treatments, sperm samples were subjected to immunocytochemistry and confocal microscopy. Positive reaction for BSP-A1/A2 was detected in the midpiece, equatorial and post-equatorial regions and acrosome, in all treatments. The signal was higher in the midpiece compared to the rest of the cells, irrespective of the treatment. The binding pattern of BSP-30kDa was similar to that observed for BSP-A1/A2. Additionally, sperm with a reacted acrosome showed a reduction in the signal of 4.9 and 3.6 times, after exposure to isthmic and ampullary fluids, respectively. OPN binding was detected in the post-equatorial region and acrosome of ejaculated sperm, with higher intensity in the acrosome. A greater amount of capacitated sperm and capable of acrosome reaction in response to LPC was seen after exposure to isthmic (39.8% and 79%) and ampullary (20.5% and 69.3%, respectively) compared to sperm exposed to MTMS alone (12.3% and 49.3%) or heparin (23.7% and 38.9%). We conclude that sperm exposure to oviductal fluids influences interactions between seminal plasma proteins and sperm membrane, possibly modulating sperm function. In Study 3, we used a proteomic approach to identify the proteins present in cauda epididymal fluid (CEF) of Holstein bulls. CEF samples were obtained from 11 bulls and used to prepare 2D gels. The spots were cut and identified using mass spectrometry. This first analysis showed that albumin composed almost 21% of the total intensity of the spots, interfering with the identification of low abundance proteins. To improve resolution, we depleted albumin from the samples using affinity spin columns and new maps were prepared. Spots detected after depletion not seen before were also identified. We observed 114 ± 3 spots before albumin detection. We identified 55 of them, comprising 23 different proteins. Based on the optical density, the most abundant proteins in the CEF samples were albumin (21.1%), cholesterol binding proteins (6 low molecular weight isoforms; 10.5%), prostaglandin D synthase (7.6%) and gelsolin (6%), accounting for 45.2% of the proteins. Another 36 spots were also identified, corresponding to 13 different proteins. After albumin depletion, the intensity of the albumin spot in the gels was reduced to 10%, and the number of spots in the maps increased to 137 ± 4. Also, 48 spots were at least 3 times more abundant after depletion. The identity of those proteins suggest a wide range of functions, including sperm metabolism regulation, changes in membrane and sperm protection against oxidative damage during epididymal storage.